(untitled) (Journal of the College of Basic Education, 2022)
This research comes within the context of the descriptive approach, which aims to study the divergent thinking skills of the students of the Mathematics Department in the Faculties of Basic Education, by answering the following questions: 1.What are the divergent thinking skills of the students of the mathematics department in the faculties of basic education? Does the performance of students in divergent thinking skills differ according to gender? The research sample was chosen by stratified random method, as the research sample consisted of (329) male and female students of the fourth stage, the Mathematics Department in the Colleges of Basic Education, at a rate of (29.67%) of the total community of (1108), distributed among (7) universities, namely (Al-Mustansiriya). Mosul, Kufa, Tikrit, Diyala, Maysan and Tal Afar). One division was selected from each of the mathematics departments in the faculties of basic education. In order to achieve the objectives of the research, the researcher took the following measures: 1 . Preparing the divergent thinking skills test, which consists of (20) paragraphs, including (15) article paragraphs and (5) objective paragraphs distributed among its four skills (open thinking, flexible thinking, original thinking, and expanded thinking), and by (5) paragraphs for each skill the four. Its validity and reliability were confirmed, as the test’s stability was (0.88). The research tool (Branded Thinking Skills Test) was applied to the basic research sample, where the application lasted for a month from Wednesday (12/30/2021) until Monday (1/24/2022), and using the appropriate statistical means, the results showed the following: Students of the Mathematics Department in the faculties of Basic Education possess a simple level of divergent thinking skills, There is a weakness in the skill of original thinking, the absence of statistically significant differences at the level of significance (0.05) due to the gender variable in divergent thinking skills. Developing divergent thinking, especially original thinking, and suggested building a training program for mathematics teachers according to divergent thinking skills, and conducting studies that investigate the impact of teaching by integrating divergent thinking skills within the academic content with other variables